Automating Open Source Intelligence. Issue 3 (March 2016) - Unknown
Abstract : Penetration testers have long known about the value of open source intelligence (OSINT). During the early stages of a penetration test – or a malicious hack, for that matter – the attacker builds a detailed picture of the target, collating everything they can from publicly available information before ever sending a packet in the target's direction.